Development of Short Story Teaching Materials Based on a Digital Magazine Containing Humanist Values for High School Students - Hidayah, Isnaini Rahmah; Nuryatin, Agus; Naryatmojo, Deby Luriawati (Universitas Negeri Semarang, 2023)
Many teaching materials were found to be less relevant to the curriculum and students' needs. Other problems were also found, such as students' attitudes showing deviations. Deviations committed by students show a lack of humanist values within themselves. It is very important to apply humanist values to students. The application of humanist values can be given to students through short story material at school. In learning, it is necessary to develop digital magazine-based teaching materials containing humanist values because high school students are generation Z who are closely related to digital technology. The aim of this research is to describe needs, create designs, validate, conduct trials, and evaluate digital magazine-based short story teaching material products containing humanist values. The research method used in this research is the Research and Development (R&D) research method by Borg and Gall which has been adapted by Sugiyono, including 6 stages. The research subjects in this study were class The data collection techniques used were observation, interview, participatory and questionnaire techniques. The data analysis techniques used are qualitative descriptive analysis and statistical tests (T-Test). The research results include three things. First, short story teaching materials based on digital magazines containing humanist values are really needed by educators and students. Second, the development design consists of three parts, namely introduction, content and conclusion. Third, the trial results show that there is an increase in student learning outcomes. Thus, digital magazine-based short story teaching materials containing humanist values are effective in increasing students' understanding in learning short story material.